The determination of chimeric secretory IGA: tb epitopes in goat milk - Mustafa, Wahidah (2023)
Tuberculosis (TB) basically has two types: active and latent infections. The current vaccination against TB, which is Bacillus Calmette-Guerin (BCG), is unable to provide protection with high efficacy against active TB while showing no protection against latent infection. The administration of BCG vaccination is systemic. Thus, the creation of mucosal tuberculosis vaccines with a focus on the protein constituent has become an area of research interest. The development of mucosal vaccines is difficult due to the nature of the mucosal system. In a previous study, our group developed the mucosal vaccine by combining the three different epitopes of TB, namely Ag85b, latency-associated protein (Acr), and resuscitation-promoting factor (Rpf) from Mycobacterium tuberculosis (Mtb), linked with secretory immunoglobulin A (sIgA). The construct has been cloned into the genome of the adeno-associated viral vector before being transduced into the mammary gland of the pregnant goat. Acr and Rpf are important components that are involved in the reactivation of dormant Mtb. Together with Ag85b, they have become important targets for the development of a new TB mucosal vaccine with the goal of preventing the reactivation of dormant tubercle bacilli associated with latent tuberculosis. In this study, the expression of the immunodominant epitope in the milk of the goat was evaluated using western blot with Rb pAb to Mycobacterium tuberculosis Ag85b. The result shows that a band at approximately 75 kDa was detected, indicating that the epitopes were successfully expressed in milk. The expression of chimeric proteins in different concentrations of goat milk is significant at p < 0.05.